Management of the Heavy Brows: Long-Term Surgical Options - Plowes Hernandez, Olga; Montes Bracchini, Jose Juan (Facial Plastic Surgery, 2018)
One of the first signs of aging belongs to the upper third of the face. With the aging process, mestizo facial features become more prominent. The thicker skin-soft tissue envelope (S-STE) has a tendency to sag more, hooding of the eyelids tends to be more pronounced, and there is a tendency for eyebrows to droop, specifically the tail of the brows, because of the loss of support. A “tired” or “sad” look implies that the complex eyebrow-upper eyelid is showing one or more of these signs. Different surgical as well as non-surgical techniques have been described to treat this area, every one of them aiming at making the patient look rested and natural. The objective of this study is to describe a technique for endoscopic brow lifting, consisting on minimal incisions, a biplanar dissection, and a different fixation technique designed for helping reshape the brow. This particular surgical technique has shown the advantage of being minimally invasive and effective. Careful analysis of the patient should be made to decide both the technique and the changes desired by the patient and the surgeon. The authors believe the technique described is another option for approaching and fixating the heavy eyebrows in mestizo patients.
Keywords: heavy brows; brow lifting; eyebrows